2020
DOI: 10.3390/agronomy10101591
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Year Dynamics of Single-Step Genomic Prediction in an Applied Wheat Breeding Program

Abstract: The availability of cost-efficient genotyping technologies has facilitated the implementation of genomic selection into numerous breeding programs. However, some studies reported a superiority of pedigree over genomic selection in line breeding, and as, aside from systematic record keeping, no additional costs are incurring in pedigree-based prediction, the question about the actual benefit of fingerprinting several hundred lines each year might suggest itself. This study aimed thus on shedding some light on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Aside from enlarging training populations, the interest of testing germplasm coming from other regions and plant breeding programs lies in the opportunity to estimate the breeding value of potential elite parents developed outside a given breeding program. Although some studies reported similar accuracies for the prediction of genomic-based and pedigree-based breeding values if phenotypic information is already available (Juliana et al, 2020;Michel et al, 2020a), producing such information would require a reallocation of resources, which are usually reserved for testing a breeder's own cultivar candidates. Furthermore, pedigree information for plant material from other programs is in most cases scarce and not systematically available, rendering the genomic selection of potential crossing parents and combinations an interesting strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from enlarging training populations, the interest of testing germplasm coming from other regions and plant breeding programs lies in the opportunity to estimate the breeding value of potential elite parents developed outside a given breeding program. Although some studies reported similar accuracies for the prediction of genomic-based and pedigree-based breeding values if phenotypic information is already available (Juliana et al, 2020;Michel et al, 2020a), producing such information would require a reallocation of resources, which are usually reserved for testing a breeder's own cultivar candidates. Furthermore, pedigree information for plant material from other programs is in most cases scarce and not systematically available, rendering the genomic selection of potential crossing parents and combinations an interesting strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic relationship information is expected to improve accuracy of PBV especially when combined with pedigree information [52,56,58,59]. It will be relatively simple to combine genomic analysis (GBLUP) and pedigree analysis (ABLUP) in single-step or hybrid BLUP (HBLUP) analysis [60][61][62][63]. GBLUP was used for selection of non-inbred progeny of wheat by Bonnett et al [64], and we expect that accuracy of PBV on non-inbred progeny will be improved further when pedigree and genomic information are combined in HBLUP.…”
Section: Discussionmentioning
confidence: 99%
“…Although the estimated experimental efficiency and accuracy was highest with complete genomic relationship information in the study at hand, a marked advantage was likewise observed when utilizing pedigree records for modelling relationship. The latter resulted in lower accuracies in comparison to a genomic prediction of non-phenotyped individuals (Auinger et al 2016;Cericola et al 2017) as the Mendelian sampling term i.e., segregation within families cannot be addressed in such a case, but pedigree best linear unbiased predictions can readily distinguish between family members if phenotypic observations are already available for them (Michel et al 2020).…”
Section: Discussionmentioning
confidence: 99%